WATER SHORTAGES ARE ONE OF THE NEGATIVE FACTORS OF OUR TIME - Madraim Khasanovich Sarikulov; Irina Viktorovna Skuratovich; Bakhodir Maratovich Bekimbetov (Modern American Journals, 2025)
This article examines drinking water shortages as a contemporary negative factor in the context of socioeconomic development, energy and food production, healthy ecosystems, and human survival. It also examines issues related to improving clean water supply in various countries. Furthermore, it highlights the challenges of water shortages in light of global population growth, which has significantly increased water consumption. It also highlights the factors that contributed to water shortages, which subsequently led to deteriorating living conditions and slowed the economic development of water-stressed countries.
Keywords: UN General Assembly, poor-quality water, Sustainable Development Goals, water disasters, population migration, interstate conflicts, dehydration, contaminated water, unsanitary conditions, disease spread.